Environmental Drivers of Adult Seasonality and Abundance of Biting Midges Culicoides (Diptera: Ceratopogonidae), Bluetongue Vector Species in Spain. Issue 1 (4th September 2020) - Barceló, Carlos; Purse, Bethan V; Estrada, Rosa; Lucientes, Javier; Miranda, Miguel Á; Searle, Kate R
Abstract: Bluetongue is a viral disease affecting wild and domestic ruminants transmitted by several species of biting midges Culicoides Latreille. The phenology of these insects were analyzed in relation to potential environmental drivers. Data from 329 sites in Spain were analyzed using Bayesian Generalized Linear Mixed Model (GLMM) approaches. The effects of environmental factors on adult female seasonality were contrasted. Obsoletus complex species (Diptera: Ceratopogonidae) were the most prevalent across sites, followed by Culicoides newsteadi Austen (Diptera: Ceratopogonidae). Activity of female Obsoletus complex species was longest in sites at low elevation, with warmer spring average temperatures and precipitation, as well as in sites with high abundance of cattle. The length of the Culicoides imicola Kieffer (Diptera: Ceratopogonidae) female adult season was also longest in sites at low elevation with higher coverage of broad-leaved vegetation. Long adult seasons of C. newsteadi were found in sites with warmer autumns and higher precipitation, high abundance of sheep. Culicoides pulicaris (Linnaeus) (Diptera: Ceratopogonidae) had longer adult periods in sites with a greater number of accumulated degree days over 10°C during winter. These results demonstrate the eco-climatic and seasonal differences among these four taxa in Spain, which may contribute to determining sites with suitable environmental circumstances for each particular species to inform assessments of the risk of Bluetongue virus outbreaks in this region.